2015
DOI: 10.1080/02102412.2015.1016716
|View full text |Cite
|
Sign up to set email alerts
|

The pan-European holiday effect

Abstract: The construction of a single European block in the context of financial markets has caused the different national stock exchanges of the euro area to converge towards one common trading calendar that allows to study whether the holiday effect is a panEuropean calendar anomaly or country-specific. By applying simulation methods, we provide evidence of the existence of statistically and economically abnormal positive pre-and post-holiday returns in the Eurozone which are not related to higher than average levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
(37 reference statements)
0
3
0
2
Order By: Relevance
“…The days leading up to and following the Federal holidays have lower volatility and a higher return mean than days during a week without a holiday. This is from the higher activity on the market from the traders who are unloading their shares and those who are buying shares (Carchano & Pardo, 2015). The short-term and long-term traders are the reasons for this.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The days leading up to and following the Federal holidays have lower volatility and a higher return mean than days during a week without a holiday. This is from the higher activity on the market from the traders who are unloading their shares and those who are buying shares (Carchano & Pardo, 2015). The short-term and long-term traders are the reasons for this.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Literature on the stock market is inundated with various forms of calendar anomalies studied across economies—turn-of-the-year effect, month-of-the-year effect, turn-of-the-month effect, day-of-the-week effect, holiday effect, Halloween effect, Friday the 13th effect, etc. (Auer & Rottmann, 2014; Carchano & Pardo, 2015; Jacobsen & Visaltanachoti, 2009; Kayacetin & Lekpek, 2016; Ng & Wang, 2004; Raj & Kumari, 2006; Singh, 2014). Seasonal patterns have been reported in other markets and series as well—national businesses and economic series (Cleveland & Devlin, 1980), petrol prices (Mitchell, Ong, & Izan, 2000), money market (Washer, Nippani, & Wingender, 2011), real estate investment trusts (Khaled & Keef, 2012), bonds (Compton, Kunkel, & Kuhlemeyer, 2013), currency market (Kumar & Pathak, 2016) and so on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition to the diverse findings of researchers in the past, the methodologies employed for these findings are equally diverse. While the ordinary least square (OLS)-based dummy variable regression equation was initially the conventional methodology in the literature on anomalies (Arsad & Coutts, 1997), several methodologies have been tested over time—the analysis of variance (ANOVA) (Mittal & Jain, 2009; Rogalski, 1984), the autoregressive conditionally heteroskedastic (ARCH) model and its variants (Abalala & Sollis, 2015; Akyol, 2011; Baker, Rahman, & Saadi, 2008; Jaisinghani, 2016; Kayacetin & Lekpek, 2016; Zhang & Li, 2006), event study (Bialkowski, Etebari, & Wisniewski, 2012), non-parametric tests (Carchano & Pardo, 2015; Elango & Macki, 2008; Mitchell et al, 2000), stochastic dominance (Al-Khazali, 2008) and so on. Zhang and Li (2006) reported that calendar anomaly was subject to sample selection and the methodology utilised.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bu nedenle, nedenselliğin test edilmesinden önce serilerin, mevsimsel etkilerden arındırılması önerilmektedir. Yapılan çalışmalara göre, finansal serilerde gözlemlenen mevsimsel etkilerin genellikle, "Haftanın Günü Etkisi" ve "Yılın Ayı Etkisi" olduğundan bahsedilmektedir (Brusa & Liu, 2004;Ng & Wang, 2004;Jefferis & Smith, 2005;Raj & Kumari, 2006;Chukwuogor, 2007;Alagidede, 2008;Choudhary & Choudhary, 2008;Patel, 2008;Jacobsen & Visaltanachoti, 2009;Latif vd., 2011;Ulussever vd., 2011;Berument & Dogan, 2012;Hsieh & Chen, 2012;Mbululu & Chipeta, 2012;Kalidas vd., 2013;Plimsoll vd., 2013;Dicle & Levendis, 2014;Singh, 2014;Auer & Rottmann, 2014;Archana vd., 2014;Carchano & Pardo, 2015;Kayacetin & Lekpek, 2016;Kumar & Jawa, 2016;Gupta, 2017;Kaushik, 2017;Sing & Yadav, 2019;v.b.). Bu nedenle, çalışmada nedensellikten önce getiri serilerindeki ilk olarak "Haftanın Günü Etkisi" kukla değişkenler yardımı ile araştırılmıştır.…”
Section: Analiz Sonuçlarıunclassified